Samorządowa i obywatelska współpraca transgranicznej w województwie podlaskim - Poleszczuk, Jan; Sztop-Rutkowska, Katarzyna; Porankiewicz-Żukowska, Aleksandra; Kiszkiel, Łukasz; Mejsak, Rafał Julian (2013)
Abstract: Studies presented in this publication were aimed at provide data necessary for the conducting of local government and citizenship dimension of the enlarged Polish foreign policy in Podlaskie region. The main objective was to investigate the diagnosis, as the local government units, non-governmental organizations, businesses and universities alluded cross-border cooperation with partners in Lithuania, Belarus, Ukraine and Russia (Kaliningrad). The publication indicated areas of the greatest potential, as well as barriers to such cooperation in the region. Particular attention was paid to the cooperation of these entities, combining their potentials and create joint projects